HUBUNGAN STATUS GIZI TERHADAP TERJADINYA PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA - Nuryanto, Nuryanto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
This study aims to determine the factors associated with respiratory disease in infants in the region of Palembang Social Health Center. This research is explanatory with the quantitative approach and cross sectional research design. The study population was children aged 12-59 months residing in the region of Palembang Social Health Center. The research sample totaling100 children taken by systematic random sampling. Statistical test using the chi square and logistic regression. After logistic regression test known to the most dominant factor for causing respiratory disease in infants is the immunization status OR: 149.37, nutritional status OR: 29.91, smoking status OR: 17.62, density residence OR: 8.17 and education level OR: 20.57. Concluded that the nutritional status factors, immunization status, housing density, the state of home ventilation, parental smoking status, maternal education, maternal knowledge and socioeconomic status families have meaningful relationships with ARI disease in infants.